Joint Framework for Access Control and Authentication using Blockchain over Cloud Environment (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
There is an increasing adoption of blockchain technology overdifferent environment for leveraging security features. After reviewingexisting blockchain-based approaches, it is noticed that there is still alarge scope of improvement towards data security using blockchain.Therefore, this paper considers a case study of healthcare facilities,where the sensitive information of patient are required to be accessed aswell as stored using a novel blockchain-based approach. The proposedsystem contributes towards developing a novel access control policy aswell as a cost-effective authentication policy using a simplified hashingscheme. The prime contribution of the study is to prove that without usingsophisticated encryption, it is feasible to integrate blockchain withhashing method for offering higher degree of threat mitigation measuresby proposed system.